BREAST TOMOSYNTHESIS: A BETTER MAMMOGRAPHY - Aguillar, Vera Lucia Nunes; Bauab, Selma di Pace; Belfer, Aron (Mastology, 2018)
Digital mammography is an excellent method for detecting breast cancer at an early stage, but overlap of breast structures may lead to both false-positive and false-negative results. The digital breast tomosynthesis (DBT) is addressed to overcome this limitation of conventional 2D mammography. The purpose of this study was to discuss the multiple aspects related to this new tool, including its role in breast cancer screening, through a literature review. DBT, or 3D mammography, provides a three-dimensional representation of the breast, with the ability to scroll through breast tissue in the reconstructed images, thereby reducing the effect of tissue superimposition. This leads to improved sensitivity and specificity in breast cancer screening. In diagnostic cases, tomosynthesis increases the accuracy with better characterization and localization of the lesions. Prospective and retrospective studies confirm that DBT is superior to digital mammography in breast cancer screening, with 27 to 53% increase in cancer detection and 17 to 37% reduction in false-positive recalls. A total of 40 to 49% of the cancers detected by DBT were invasive: 40 to 48% of histological grade 2 or 3 and more than 75% were node negative. DBT is the most promising new modality for breast cancer screening. Further studies are needed to evaluate the reduction of interval cancers with this modality.